Visual Records and Urban Development - Burant, Jim (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1984)
This article describes the history and the holdings of the Picture Division of the Public Archives of Canada, with especial reference to their use as documents in the history of Canada. Visual records are often the most abused and misunderstood of all archival documents because researchers do not attempt to learn more about the context of their creation or their creators. Various examples are cited to buttress this contention, and attention is paid to some books where visual records form an integral part of the subject posited. A brief listing of useful resource publications in the study of Canadian visual records are given, as well as an explanation of how to gain access to the Picture Division's collections.